Comparative evaluation of Tell-Show-Do technique and its modifications in managing anxious pediatric dental patients among 4-8 years of age - Priyanka Sunil Lekhwani; Anant Gopal Nigam; Nikhil Marwah; Shradha Jain (Wolters Kluwer Medknow Publications, 2023)
Background: Dentistry has made a remarkable progress in techniques, materials and technologies, however the anxiety of the child related to dental treatment still remains constant. Tell Show Do is the most common technique behaviour management of the child in the dental clinic since many years. Recently, many modifications of Tell Show Do technique have been researched and most of them provided an enhanced potential for the conventional technique research but were always individually compared to conventional technique. Aim: To evaluate the effectiveness of Tell Show Do technique in comparison with its 4 modifications Tell Play Do, Tell Play Do with Smart Phone Dentist Game, Tell Show Play Doh, Ask Tell Ask among 4-8 years old children during restorative treatment. Methodology: 150 children aged 4-8 years were randomly selected divided into 5 groups comprising of 30 patients each. Evaluation of anxiety was done using Physiologic-Pulse Rate, Facial Image Scale and Venham's Anxiety Scale. Results: Except for Ask Tell Ask Group the anxiety level of the subjects decreased in all groups according to physiologic readings and facial image score. Anxiety Score decreased preoperatively to postoperatively in all groups except for Tell Play Do and Ask Tell Ask group according to venhams anxiety scale. Conclusion: Although Tell Show Do technique is most widely accepted and modified technique, due to changing scenarios of today's children Tell Play Do, Tell Play Do with Smart Phone Dentist Game and Tell Show Play Doh are also showing encouraging results.